Conductive polymer-containing liquid and method of producing same, and conductive laminate and method of producing same

By formulating a conductive polymer-containing liquid with specific solvent ratios and controlled iron ion content, the challenges of dispersion stability and wettability in existing conductive polymer dispersions are addressed, resulting in a conductive laminate with enhanced conductivity and stability.

JP2025062058AActive Publication Date: 2025-04-11SHIN ETSU POLYMER CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2025016741
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-02-04
Publication Date
2025-04-11
Estimated Expiration
2041-08-26

AI Technical Summary

Technical Problem

Existing methods for creating conductive polymer dispersions face challenges with dispersion stability when combined with water-soluble organic solvents, leading to reduced wettability and conductivity over time.

Method used

A conductive polymer-containing liquid is developed, comprising a π-conjugated conductive polymer, a polyanion, and a dispersion medium of water, methanol, and isopropanol, with controlled iron ion content and solvent ratios to enhance dispersion stability and wettability.

Benefits of technology

The solution achieves excellent dispersion stability and storage stability of the conductive composite, allowing for the formation of a conductive laminate with good conductivity and wettability to various substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025062058000001
    Figure 2025062058000001
  • Figure 2025062058000002
    Figure 2025062058000002
Patent Text Reader

Abstract

To provide: a conductive polymer-containing liquid having improved dispersion stability in a conductive composite coexisting with a water-soluble organic solvent; and a method of producing the same.SOLUTION: Provided is a conductive polymer-containing liquid that contains a conductive composite containing a π-conjugated conductive polymer and polyanions, and a dispersion medium, wherein the dispersion medium comprises water, methanol, and isopropanol, and a content of iron ions is 0.34 ppm or less relative to a total mass of the conductive polymer-containing liquid. In the dispersion medium, the relationship between a content m1 of the methanol and a content m2 of the isopropanol is preferably m1<m2.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a conductive polymer-containing liquid that contains a π-conjugated conductive polymer and a method for producing the same, and a conductive laminate and a method for producing the same. [Background technology]

[0002] A conductive polymer dispersion containing a conductive complex in which a π-conjugated conductive polymer is doped with a polyanion may be used as a paint or a component thereof for forming a conductive layer. For example, poly(3,4-ethylenedioxythiophene), a π-conjugated conductive polymer, is difficult to disperse in water, but by doping it with polystyrene sulfonic acid to form PEDOT-PSS, the dispersibility in water is improved. Patent Document 1 discloses a technique for improving the hydrophilicity of a conductive complex and improving its reactivity to epoxy compounds by dispersing the conductive complex in water and leaving it for 180 days or more. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2020-31013 A Summary of the Invention [Problem to be solved by the invention]

[0004] In the method of Patent Document 1, an epoxy compound is reacted with a conductive composite, and then the composite is dissolved in an organic solvent to form a coating material, thereby enhancing wettability with respect to a hydrophobic film substrate. On the one hand, when the conductive composite is not hydrophobized by reaction with an epoxy compound, a water-soluble organic solvent such as alcohol may be added to the conductive polymer dispersion to enhance the wettability with respect to a substrate such as a film. However, the dispersion stability of the conductive composite in the paint added with the water-soluble organic solvent is low, and the dispersibility may decrease within several hours from the production, and it may become impossible to perform coating. For this reason, after adding a water-soluble organic solvent to the conductive polymer dispersion that has been subjected to dispersion treatment to obtain a paint, it is required to maintain the dispersibility of the conductive composite in the paint.

[0005] The present inventors have found that a conductive polymer-containing liquid with enhanced dispersibility of the conductive composite can be obtained by devising the combination of the content of iron ions contained in the conductive polymer dispersion used for the preparation of the paint (the conductive polymer-containing liquid described later) and the type of the water-soluble organic solvent, and have completed the present invention.

[0006] The present invention provides a conductive polymer-containing liquid in which the dispersion stability of the conductive composite coexisting with the water-soluble organic solvent is improved, and a method for producing the same. Further, a conductive laminate formed using the conductive polymer-containing liquid and a method for producing the same are provided.

Means for Solving the Problems

[0007] [1] A conductive polymer-containing liquid containing a conductive composite containing a π-conjugated conductive polymer and a polyanion and a dispersion medium, wherein the dispersion medium includes water, methanol, and isopropanol, and the content of iron ions with respect to the total mass of the conductive polymer-containing liquid is 0.34 ppm or less. [2] The conductive polymer-containing liquid according to [1], wherein the relationship between the content mass m1 of methanol and the content mass m2 of isopropanol in the dispersion medium is m1 < m2. [3] The conductive polymer-containing liquid according to [1] or [2], wherein the total content ratio of the content mass m1 of methanol and the content mass m2 of isopropanol with respect to the total mass of the dispersion medium is 60% by mass or more. [4] The conductive polymer-containing liquid according to any one of [1] to [3], wherein the content of the water (m3) relative to the total mass of the dispersion medium is 10 mass % or more. [5] The conductive polymer-containing liquid according to any one of [1] to [4], wherein a total content of the methanol by mass m1, the isopropanol by mass m2, and the water by mass m3 relative to a total mass of the dispersion medium is 90 mass% or more. [6] The conductive polymer-containing liquid according to any one of [1] to [5], further comprising a binder component. [7] The conductive polymer-containing liquid according to any one of [1] to [5], wherein the π-conjugated conductive polymer is poly(3,4-ethylenedioxythiophene) or the polyanion is polystyrenesulfonic acid. [8] A method for producing a conductive polymer-containing liquid, comprising the steps of: obtaining a conductive polymer dispersion liquid (A) containing a conductive complex containing the π-conjugated conductive polymer and the polyanion, the aqueous dispersion medium, and the iron ions by polymerizing the monomer in a reaction liquid containing a polyanion, an aqueous dispersion medium, a monomer forming a π-conjugated conductive polymer, and iron ions; adding a cation exchange resin to the conductive polymer dispersion liquid (A) to adsorb at least a portion of the iron ions, and then removing the cation exchange resin to obtain a conductive polymer dispersion liquid (B); and adding at least methanol and isopropanol to the conductive polymer dispersion liquid (B) to obtain a conductive polymer-containing liquid, wherein a content of the iron ions relative to the total mass of the conductive polymer dispersion liquid (B) is 10 ppm or less, and a content of the iron ions relative to the total mass of the conductive polymer-containing liquid is 0.34 ppm. [9] A conductive laminate comprising a film substrate, and a conductive layer formed on one surface of the film substrate, the conductive layer being a cured layer of the conductive polymer-containing liquid according to any one of [1] to [7], and optionally comprising a pressure-sensitive adhesive layer on the other surface of the film substrate.

[10] A method for producing a conductive laminate, comprising applying the conductive polymer-containing liquid according to any one of [1] to [7] to at least a partial surface of a substrate. Effect of the Invention

[0008] According to the method for producing a conductive polymer-containing liquid of the present invention, a conductive polymer-containing liquid having excellent dispersion stability of the conductive complex can be easily produced. The conductive polymer-containing liquid of the present invention has excellent dispersion stability, in other words, excellent storage stability. According to the method for producing a conductive laminate of the present invention, the conductive polymer-containing liquid used has excellent dispersion stability and excellent wettability to the substrate, so that the conductive laminate can be easily produced. The conductive laminate of the present invention has a conductive layer with good conductivity.

[0009] This invention is believed to contribute to SDGs Goal 12, "Responsible Consumption and Production." DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] In this specification and claims, the lower limit and upper limit of a numerical range indicated with "to" are included in the numerical range.

[0011] ≪Conductive polymer-containing liquid≫ A first aspect of the present invention is a conductive polymer-containing liquid containing a conductive complex containing a π-conjugated conductive polymer and a polyanion, and a dispersion medium. The dispersion medium contains water, methanol, and isopropanol. The conductive polymer-containing liquid has an iron ion content of 0.34 ppm or less relative to the total mass of the conductive polymer-containing liquid. In the conductive polymer-containing liquid of this embodiment, the conductive complex may be in a dispersed state or in a dissolved state, and no distinction is made between the two unless otherwise specified.

[0012] <π-conjugated conductive polymers> The π-conjugated conductive polymer is not particularly limited as long as it has the effect of the present invention and is an organic polymer whose main chain is composed of a π-conjugated system, and examples thereof include polypyrrole-based conductive polymers, polythiophene-based conductive polymers, polyacetylene-based conductive polymers, polyphenylene-based conductive polymers, polyphenylenevinylene-based conductive polymers, polyaniline-based conductive polymers, polyacene-based conductive polymers, polythiophenevinylene-based conductive polymers, and copolymers thereof. From the viewpoint of stability in air, polypyrrole-based conductive polymers, polythiophenes, and polyaniline-based conductive polymers are preferred, and from the viewpoint of transparency, polythiophene-based conductive polymers are more preferred.

[0013] Polythiophene-based conductive polymers include polythiophene, poly(3-methylthiophene), poly(3-ethylthiophene), poly(3-propylthiophene), poly(3-butylthiophene), poly(3-hexylthiophene), poly(3-heptylthiophene), poly(3-octylthiophene), poly(3-decylthiophene), poly(3-dodecylthiophene), poly(3-octadecylthiophene), poly(3-bromothiophene), poly(3-chlorothiophene), and poly(3-iodothiophene). thiophene), poly(3-cyanothiophene), poly(3-phenylthiophene), poly(3,4-dimethylthiophene), poly(3,4-dibutylthiophene), poly(3-hydroxythiophene), poly(3-methoxythiophene), poly(3-ethoxythiophene), poly(3-butoxythiophene), poly(3-hexyloxythiophene), poly(3-heptyloxythiophene), poly(3-octyloxythiophene), poly(3-decyloxythiophene), poly(3-dodecyloxythiophene), oxythiophene), poly(3-octadecyloxythiophene), poly(3,4-dihydroxythiophene), poly(3,4-dimethoxythiophene), poly(3,4-diethoxythiophene), poly(3,4-dipropoxythiophene), poly(3,4-dibutoxythiophene), poly(3,4-dihexyloxythiophene), poly(3,4-diheptyloxythiophene), poly(3,4-dioctyloxythiophene), poly(3,4-didecyloxythiophene), poly(3,4-di dodecyloxythiophene), poly(3,4-ethylenedioxythiophene), poly(3,4-propylenedioxythiophene), poly(3,4-butylenedioxythiophene), poly(3-methyl-4-methoxythiophene), poly(3-methyl-4-ethoxythiophene), poly(3-carboxythiophene), poly(3-methyl-4-carboxythiophene), poly(3-methyl-4-carboxyethylthiophene), and poly(3-methyl-4-carboxybutylthiophene). Examples of polypyrrole-based conductive polymers include polypyrrole, poly(N-methylpyrrole), poly(3-methylpyrrole), poly(3-ethylpyrrole), poly(3-n-propylpyrrole), poly(3-butylpyrrole), poly(3-octylpyrrole), poly(3-decylpyrrole), poly(3-dodecylpyrrole), poly(3,4-dimethylpyrrole), poly(3,4-dibutylpyrrole), poly(3-carboxypyrrole), poly(3-methyl-4-carboxypyrrole), poly(3-methyl-4-carboxyethylpyrrole), poly(3-methyl-4-carboxybutylpyrrole), poly(3-hydroxypyrrole), poly(3-methoxypyrrole), poly(3-ethoxypyrrole), poly(3-butoxypyrrole), poly(3-hexyloxypyrrole), and poly(3-methyl-4-hexyloxypyrrole). Examples of polyaniline-based conductive polymers include polyaniline, poly(2-methylaniline), poly(3-isobutylaniline), poly(2-anilinesulfonic acid), and poly(3-anilinesulfonic acid). Among the above-mentioned π-conjugated conductive polymers, poly(3,4-ethylenedioxythiophene) is particularly preferable from the viewpoints of conductivity, transparency, and heat resistance. The conductive composite may contain one type of π-conjugated conductive polymer, or two or more types of polymers.

[0014] <Polyanion> A polyanion is a polymer having two or more monomer units each having an anionic group in the molecule. The anionic group of the polyanion functions as a dopant for a π-conjugated conductive polymer, improving the conductivity of the π-conjugated conductive polymer. The anion group of the polyanion is preferably a sulfo group or a carboxy group. Specific examples of such polyanions include polymers having a sulfo group, such as polystyrene sulfonic acid, polyvinyl sulfonic acid, polyallyl sulfonic acid, polyacrylic acid esters having a sulfo group, polymethacrylic acid esters having a sulfo group (for example, poly(4-sulfobutyl methacrylate, polysulfoethyl methacrylate, polymethacryloyloxybenzenesulfonic acid), poly(2-acrylamido-2-methylpropanesulfonic acid), and polyisoprene sulfonic acid; and polymers having a carboxy group, such as polyvinyl carboxylic acid, polystyrene carboxylic acid, polyallyl carboxylic acid, polyacrylic acid, polymethacrylic acid, poly(2-acrylamido-2-methylpropanecarboxylic acid), and polyisoprene carboxylic acid. These may be homopolymers or copolymers of two or more kinds. Among these polyanions, polymers having a sulfo group are preferred, and polystyrene sulfonic acid is more preferred, since they can provide higher electrical conductivity. The conductive complex may be composed of one type of polyanion or two or more types of polyanions. The mass average molecular weight of the polyanion is preferably from 20,000 to 1,000,000, more preferably from 100,000 to 500,000. The mass average molecular weight is the average molecular weight based on mass measured by gel permeation chromatography and calculated in terms of polystyrene.

[0015] A conductive complex is formed by doping a polyanion into a π-conjugated conductive polymer. However, in the polyanion, some anion groups are not doped into the π-conjugated conductive polymer, and there are excess anion groups that are not involved in the doping. Since these excess anion groups are hydrophilic groups, the conductive complex has high water dispersibility and low organic solvent dispersibility unless the iron ion content is adjusted as described below. When the number of all anionic groups in the polyanion is taken as 100 mol %, the excess anionic groups are preferably from 30 mol % to 90 mol %, more preferably from 45 mol % to 75 mol %.

[0016] In the conductive polymer-containing liquid of this embodiment, the content ratio of the polyanion is preferably in the range of 1 part by mass or more and 1000 parts by mass or less, more preferably 10 parts by mass or more and 700 parts by mass or less, and even more preferably 100 parts by mass or more and 500 parts by mass or less with respect to 100 parts by mass of the π-conjugated conductive polymer. If the content ratio of the polyanion is equal to or higher than the lower limit value, the doping effect on the π-conjugated conductive polymer tends to be enhanced, and the conductivity becomes higher. On the other hand, if the content of the polyanion is equal to or lower than the upper limit value, the amount of anion groups not involved in doping is appropriately suppressed, and it becomes easy to disperse the conductive composite in a dispersion medium containing isopropanol at a predetermined iron ion content.

[0017] As the content of the π-conjugated conductive polymer and the polyanion with respect to the total mass of the conductive polymer-containing liquid of this embodiment, 0.001% by mass or more and 1.0% by mass or less is preferable, 0.01% by mass or more and 0.5% by mass or less is more preferable, 0.02% by mass or more and 0.1% by mass or less is even more preferable, and 0.03% by mass or more and 0.05% by mass or less is particularly preferable. When it is equal to or higher than the lower limit value of the above range, the conductivity of the conductive layer formed by applying the conductive polymer-containing liquid can be further improved. When it is equal to or lower than the upper limit value of the above range, the dispersibility of the conductive composite in the conductive polymer-containing liquid can be enhanced, and a uniform conductive layer can be formed.

[0018] <Dispersion medium> The dispersion medium contained in the conductive polymer-containing liquid of this embodiment is a liquid agent that disperses or dissolves the above-mentioned conductive composite. In this specification, there are cases where dispersion and dissolution are not distinguished and simply referred to as dispersion, and there are cases where the dispersion medium and the solvent are not distinguished and simply referred to as the dispersion medium. Therefore, the dispersion medium may be referred to as a solvent.

[0019] The dispersion medium of this embodiment contains water, methanol, and isopropanol. In the dispersion medium of this embodiment, the relationship between the content mass m1 of methanol and the content mass m2 of isopropanol can be m1 < m2. Even with this relationship, the dispersion stability of the conductive composite can be sufficiently enhanced. In the dispersion medium of this embodiment, the mass ratio of the methanol content m1 to the isopropanol content m2, expressed as (m1 / m2), is preferably 0.1 to 0.9, more preferably 0.2 to 0.8, and even more preferably 0.3 to 0.7. When in the above preferred range, the dispersion stability of the conductive composite is further improved. The total content of the methanol content m1 and the isopropanol content m2 relative to the total mass of the dispersion medium in this embodiment is preferably 60 mass% or more, more preferably 65 mass% or more, and even more preferably 70 mass% or more. When in the above preferred range, the wettability of the conductive polymer-containing liquid to the substrate is improved, and a uniform conductive layer can be easily formed. The content of water (m3) relative to the total mass of the dispersion medium in this embodiment is preferably 10% by mass or more, more preferably 15% by mass or more, and even more preferably 20% by mass or more. When in the above preferred range, the dispersion stability of the conductive composite is further improved. The total content of the methanol content m1, the isopropanol content m2, and the water content m3 relative to the total mass of the dispersion medium in this embodiment is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 98% by mass or more. When in the above preferred range, the dispersion stability of the conductive composite is further improved.

[0020] The dispersion medium of this embodiment may contain a solvent (other solvent) other than water, methanol, and isopropanol. The other solvent is preferably a water-soluble organic solvent, which dissolves in 100 g of water at 20° C. in an amount of 1 g or more.

[0021] Examples of the water-soluble organic solvent include alcohol-based solvents, ether-based solvents, ketone-based solvents, nitrogen atom-containing solvents, and ester-based solvents. Examples of alcohol-based solvents (alcohols) include ethanol, 1-propanol, 2-methyl-2-propanol, 1-butanol, 2-butanol, 2-methyl-1-propanol, allyl alcohol, ethylene glycol, propylene glycol, propylene glycol monomethyl ether, and ethylene glycol monomethyl ether. Examples of the ether solvent include diethyl ether, dimethyl ether, propylene glycol dialkyl ether, and diethylene glycol diethyl ether. Examples of the ketone solvent include diethyl ketone, methyl propyl ketone, methyl butyl ketone, methyl isopropyl ketone, methyl isobutyl ketone, methyl amyl ketone, diisopropyl ketone, methyl ethyl ketone, acetone, and diacetone alcohol. Examples of the nitrogen atom-containing solvent include N-methylpyrrolidone, dimethylacetamide, and dimethylformamide. The water-soluble organic solvent may be used alone or in combination of two or more kinds.

[0022] (iron ion content) The content of iron ions relative to the total mass of the conductive polymer-containing liquid of this embodiment is 0.34 ppm or less, preferably 0.28 ppm or less, more preferably 0.24 ppm or less, even more preferably 0.20 ppm or less, may be 0.15 ppm or less, may be 0.10 ppm or less, may be 0.05 ppm or less, or may be 0 ppm. When the content is within the above preferred range, the dispersion stability of the conductive composite is further improved. The content of iron ions contained in the conductive polymer-containing liquid of this embodiment is determined by ICP emission spectrometry. 2+ and Fe 3+ The total amount of both is regarded as the iron ion content without distinction.

[0023] <Binder components> The conductive polymer-containing liquid of this embodiment may contain a binder component. The binder component is a resin other than the π-conjugated conductive polymer and the polyanion or a precursor thereof, and is a thermoplastic resin, or a curable monomer or oligomer that is cured when the conductive layer is formed. The thermoplastic resin becomes the binder resin as it is, and the curable monomer or oligomer becomes the resin formed by curing becomes the binder resin. The binder component may be one type only, or two or more types may be included.

[0024] Specific examples of binder resins derived from binder components include acrylic resins (acrylic compounds), polyester resins, polyurethane resins, polyimide resins, polyether resins, melamine resins, and silicones. The binder resin contained in the conductive polymer-containing liquid of this embodiment is preferably a water-dispersible resin, more preferably a water-dispersible emulsion resin. The water-dispersible resin is an emulsion resin or a water-soluble resin.

[0025] Specific examples of water-dispersible emulsion resins include acrylic resins (acrylic compounds), polyester resins, polyurethane resins, polyimide resins, melamine resins, and the like, which are emulsionized with an emulsifier.

[0026] Since the strength of a coating film formed by applying the conductive polymer-containing liquid of this embodiment to a substrate is increased, the binder resin preferably contains a resin having an epoxy group, more preferably contains an acrylic resin having an epoxy group, and further preferably contains an emulsion of an acrylic resin having an epoxy group.

[0027] In order to increase the strength of the coating film formed by coating the conductive polymer-containing liquid of this embodiment on a substrate, the binder resin preferably contains a polyester resin, more preferably contains an emulsion of a polyester resin. In particular, when the binder resin is applied to a polyester film substrate, the binder resin preferably contains a polyester resin or an emulsion thereof, since the adhesiveness of the coating film to the substrate is increased. The combined use of the above acrylic resin and polyester resin is preferred since it further increases the strength and adhesion of the coating film.

[0028] Specific examples of the water-soluble resin include acrylic resin (acrylic compound), polyester resin, polyurethane resin, polyimide resin, and melamine resin, which have an acid group such as a carboxy group or a sulfo group or a salt thereof. Here, the water-soluble resin is preferably one that dissolves in an amount of 1 g or more, preferably 5 g or more, and more preferably 10 g or more in 100 g of distilled water at 25° C. The acid group, such as a carboxy group or a sulfo group, contained in the water-dispersible resin may form a salt with a cation, such as a sodium ion or a potassium ion.

[0029] The binder component may be a curable monomer or oligomer, which may be a thermosetting monomer or oligomer, or may be a photocurable monomer or oligomer. Here, the oligomer refers to a polymer having a mass average molecular weight of less than 10,000. Note that a polymer having a mass average molecular weight of more than 10,000 does not have curability. Examples of the curable monomer include an acrylic monomer (acrylic compound), an epoxy monomer, an organosiloxane, etc. Examples of the curable oligomer include an acrylic oligomer (acrylic compound), an epoxy oligomer, a silicone oligomer (curable silicone), etc. When an acrylic monomer or an acrylic oligomer is used as the binder component, it can be easily cured by heating or light irradiation. When an organosiloxane or a silicone oligomer is used as the binder component, it is possible to impart releasability (non-adhesiveness) to the conductive layer.

[0030] When the composition contains a curable monomer or oligomer, it is preferable to further contain a curing catalyst. For example, when the composition contains a thermosetting monomer or oligomer, it is preferable to contain a thermal polymerization initiator that generates radicals by heating, and when the composition contains a photocurable monomer or oligomer, it is preferable to contain a photopolymerization initiator that generates radicals by light irradiation. In addition, when the composition contains an organosiloxane or silicone oligomer, it is preferable to contain a platinum catalyst for curing.

[0031] The content ratio of the binder component in the conductive polymer-containing liquid of this embodiment is preferably 100 parts by mass or more and 20,000 parts by mass or less, more preferably 500 parts by mass or more and 10,000 parts by mass or less, and even more preferably 1,000 parts by mass or more and 5,000 parts by mass or less, relative to 100 parts by mass of the conductive composite. When the content is equal to or greater than the lower limit of the above range, the film formability and film strength can be improved when the conductive polymer-containing liquid of this embodiment is applied to a substrate. When the content is equal to or less than the upper limit of the above range, a decrease in electrical conductivity due to a decrease in the content ratio of the conductive complex can be suppressed.

[0032] (Other additives) The conductive polymer-containing liquid of this embodiment may contain other known additives. Examples of the additives that can be used include surfactants, inorganic conductive agents, antifoaming agents, coupling agents, antioxidants, and ultraviolet absorbing agents. The surfactant may be a nonionic, anionic or cationic surfactant, with the nonionic surfactant being preferred from the standpoint of storage stability. A polymer surfactant such as polyvinylpyrrolidone may also be added. Examples of the inorganic conductive agent include metal ions, conductive carbon, etc. Metal ions can be generated by dissolving a metal salt in water. The antifoaming agent includes silicone resin, polydimethylsiloxane, silicone oil, and the like. The coupling agent may be a silane coupling agent having a vinyl group or an amino group. Examples of the ultraviolet absorber include benzotriazole-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers, salicylate-based ultraviolet absorbers, cyanoacrylate-based ultraviolet absorbers, oxanilide-based ultraviolet absorbers, hindered amine-based ultraviolet absorbers, and benzoate-based ultraviolet absorbers. When the above-mentioned additives are contained, the content ratio is appropriately determined depending on the type of additive, but can be, for example, in the range of 0.001 parts by mass or more and 5 parts by mass or less per 100 parts by mass of the conductive composite.

[0033] <Method for producing conductive polymer-containing liquid> The second aspect of the present invention includes the following first to third steps: The conductive polymer-containing liquid of the first aspect can be obtained by the production method of this aspect. The first step is a step of obtaining a conductive polymer dispersion liquid (A) containing a conductive complex containing the π-conjugated conductive polymer and the polyanion, the aqueous dispersion medium, and the iron ions by polymerizing the monomer in a reaction liquid containing the polyanion, an aqueous dispersion medium, a monomer that forms a π-conjugated conductive polymer, and iron ions. The second step is a step of adding a cation exchange resin to the conductive polymer dispersion (A) to adsorb at least a portion of the iron ions, and then removing the cation exchange resin to obtain a conductive polymer dispersion (B). The third step is a step of adding at least methanol and isopropanol to the conductive polymer dispersion liquid (B) to obtain a conductive polymer-containing liquid. The content by mass of the iron ions relative to the total mass of the conductive polymer dispersion (B) obtained in the second step is preferably 10 ppm or less. The content of the iron ions relative to the total mass of the conductive polymer-containing liquid obtained in the third step is preferably 0.34 ppm or less, and more preferably the suitable content described in the first embodiment.

[0034] (first step) The polyanion used in the first step is the same as the polyanion in the first embodiment, and therefore a duplicated description will be omitted here. The monomer used in the first step can be a known monomer that forms the aforementioned π-conjugated conductive polymer.

[0035] The aqueous dispersion medium constituting the reaction liquid is a solvent that dissolves the polyanion and the monomer, and contains at least water and may further contain a water-soluble organic solvent. Specific examples of the water-soluble organic solvent are the same as those described above. The water content relative to the total mass of the aqueous dispersion medium is preferably 60% by mass or more and 100% by mass or less, more preferably 70% by mass or more and 100% by mass or less, even more preferably 80% by mass or more and 100% by mass or less, and particularly preferably 90% by mass or more and 100% by mass or less. When the amount is within the above preferred range, the polymerization reaction of the monomers can proceed stably.

[0036] The iron ions contained in the reaction solution can function as a catalyst for the polymerization reaction of the monomer. Therefore, it is preferable that the reaction solution contains a catalyst containing iron ions. Specific examples of the catalyst include ferric chloride, ferric sulfate, and ferric nitrate. Among them, ferric sulfate is preferable because it stably polymerizes the monomer at room temperature. The content of the catalyst is preferably from 0.001% by mass to 2.0% by mass, more preferably from 0.01% by mass to 1.0% by mass, and even more preferably from 0.1% by mass to 0.5% by mass, based on the total mass of the reaction liquid. Within the above preferred range, the polymerization reaction can proceed stably.

[0037] The reaction liquid preferably contains an oxidizing agent together with the catalyst. The oxidizing agent is capable of polymerizing the monomer. Examples of the oxidizing agent include persulfates such as ammonium persulfate, sodium persulfate, and potassium persulfate. The oxidizing agent is preferably dissolved in ion-exchanged water in advance as an oxidizing agent solution, and is then slowly added to the reaction liquid. The concentration of the oxidizing agent solution is preferably 0.5% by mass or more and 2.0% by mass or less.

[0038] The temperature of the reaction liquid obtained after the addition of the oxidizing agent solution is preferably kept at 5 to 30° C. while carrying out the polymerization reaction. The reaction time required for the reaction in the reaction solution to be completed is approximately 4 to 12 hours, and the reaction is preferably completed within 6 to 10 hours. The completion of the polymerization reaction can be confirmed by confirming by gas chromatography that the monomers have been completely consumed.

[0039] (Second process) The conductive polymer dispersion (A) obtained in the first step contains iron ions. Examples of the method for removing at least a part of the iron ions in this step include a method of contacting the conductive polymer dispersion (A) with an ion exchange resin to adsorb the iron ions to the ion exchange resin, and a method of ultrafiltrating the conductive polymer dispersion (A) to replace the aqueous dispersion medium and remove the iron ions. Among these, the method using an ion exchange resin is preferable because it is simple. As the ion exchange resin, it is preferable to use at least a cation exchange resin out of a cation exchange resin and an anion exchange resin. The anion exchange resin can adsorb the counter anion of the iron ion.

[0040] In this step, a conductive polymer dispersion liquid (B) from which at least a portion of the iron ions have been removed is obtained. The content of iron ions relative to the total mass of the conductive polymer dispersion liquid (B) is preferably 10 ppm or less, more preferably 8 ppm or less, and even more preferably 6 ppm or less. When the content is within the above preferred range, it becomes easier to adjust the iron ion content in the conductive polymer-containing liquid obtained in the later step to a desired range.

[0041] (Third step) By adding at least methanol and isopropanol to the conductive polymer dispersion liquid (B) obtained in the second step, the conductive polymer-containing liquid of the first embodiment can be obtained. The amount and ratio of methanol and isopropanol to be added are preferably the same as those described in the first embodiment. In addition to methanol and isopropanol, it is preferable to add an appropriate amount of water. Other solvents may also be added.

[0042] The conductive polymer-containing liquid thus obtained is preferably stirred to disperse the conductive composite. The stirring method is not particularly limited, and may be a stirrer or the like that exerts a weak shearing force, or may be a high-pressure homogenizer or other dispersing device that exerts a high shearing force, but it is preferable to use a high-pressure homogenizer or the like in order to improve dispersibility.

[0043] (Optional ingredient addition) A binder component and other additives may be further added to the obtained conductive polymer-containing liquid.

[0044] <Conductive laminate> A third aspect of the present invention is a conductive laminate comprising a substrate and a conductive layer formed on at least a portion of the surface of the substrate, the conductive layer being a cured layer of the conductive polymer-containing liquid of the first aspect.

[0045] [Conductive layer] The conductive layer may be formed on the entire surface of any surface of the substrate, or on only a part of the surface. When the substrate is a film substrate, the conductive laminate becomes a conductive film. In the conductive film, it is preferable that a conductive layer of substantially uniform thickness is formed on substantially the entire surface of one side or the other side of the film substrate. When the conductive layer is formed only on a part of the surface of the substrate, for example, the conductive layer may be a fine conductive pattern such as a circuit or an electrode, or the conductive layer may be provided on the same surface and the conductive layer may be not provided on the same surface and may be roughly divided.

[0046] The average thickness of the conductive layer is, for example, preferably 10 nm or more and 100 μm or less, more preferably 20 nm or more and 50 μm or less, and even more preferably 30 nm or more and 30 μm or less. When the average thickness of the conductive layer is equal to or greater than the lower limit, high conductivity can be exhibited, and when the average thickness is equal to or less than the upper limit, the adhesion of the conductive layer to the substrate is further improved. The average thickness of the conductive layer is calculated by measuring the thickness at 10 randomly selected points and averaging the measured values.

[0047] [Adhesive layer] When a conductive layer is formed on one side of the film substrate, a pressure-sensitive adhesive layer may be provided on the other side of the film substrate. In other words, the pressure-sensitive adhesive layer is an optional layer that may or may not be present. The average thickness of the pressure-sensitive adhesive layer is, for example, preferably 1 nm or more and 1000 μm or less, more preferably 5 nm or more and 500 μm or less, and even more preferably 10 nm or more and 100 μm or less. When it is at least the lower limit of the above range, sufficient adhesiveness is obtained, and when it is at most the upper limit of the above range, the adhesion of the adhesive layer to the substrate is further improved. The average thickness of the pressure-sensitive adhesive layer is calculated by measuring the thickness at 10 randomly selected points and averaging the measured values.

[0048] The degree of adhesiveness of the adhesive is not particularly limited, and may be adhesive enough to be easily peeled off by hand after application, or may be adhesive enough to be difficult to peel off after application. Adhesiveness that is difficult to peel off can be rephrased as adhesiveness. In other words, the adhesiveness may be such that it is possible to adhere semi-permanently.

[0049] (Acrylic adhesive) As the pressure-sensitive adhesive, a known pressure-sensitive adhesive can be used, and an example of the pressure-sensitive adhesive is an acrylic pressure-sensitive adhesive. The acrylic adhesive can bond and integrate the surfaces of the same or different solids. The acrylic adhesive contains an acrylic resin (acrylic polymer).

[0050] Specific examples of acrylic monomers that form acrylic resins include acrylic acid, methacrylic acid, methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, butyl methacrylate, 2-ethylhexyl acrylate, 2-methoxyethyl acrylate, ditrimethylolpropane tetraacrylate, 2-hydroxy-3-phenoxypropyl acrylate, bisphenol A·ethylene oxide modified diacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate, dipentaerythritol monohydroxypentaacrylate, dipropylene glycol diacrylate, trimethylolpropane triacrylate, glycerol propoxy triacrylate, 4-hydroxybutyl acrylate, 1,6-hexanediol diacrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, acrylate, isobornyl acrylate, polyethylene glycol diacrylate, pentaerythritol triacrylate, tetrahydrofurfuryl acrylate, tripropylene glycol diacrylate, and other acrylates; methacrylates, such as tetraethylene glycol dimethacrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, t-butyl methacrylate, allyl methacrylate, 1,3-butylene glycol dimethacrylate, benzyl methacrylate, cyclohexyl methacrylate, diethylene glycol dimethacrylate, 2-ethylhexyl methacrylate, glycidyl methacrylate, 1,6-hexanediol dimethacrylate, 2-hydroxyethyl methacrylate, isobornyl methacrylate, lauryl methacrylate, phenoxyethyl methacrylate, tetrahydrofurfuryl methacrylate, and trimethylolpropane trimethacrylate, and other methacrylates;Examples of (meth)acrylamides include diacetone acrylamide, N,N-dimethylacrylamide, dimethylaminopropyl acrylamide, dimethylaminopropyl methacrylamide, methacrylamide, N-methylolacrylamide, acryloylformolin, N-methylacrylamide, N-isopropylacrylamide, Nt-butylacrylamide, N-phenylacrylamide, acryloylpiperidine, and 2-hydroxyethylacrylamide. The acrylic resin may be formed of one type of acrylic monomer or two or more types of acrylic monomers. By combining two or more types of acrylic monomers, the adhesiveness can be adjusted.

[0051] The acrylic resin may be a copolymer of an acrylic monomer and a vinyl monomer other than the acrylic monomer. Examples of vinyl monomers include styrene, α-methylstyrene, vinyl acetate, acrylonitrile, methacrylonitrile, and maleic anhydride. The content of the acrylic monomer unit in the copolymer is preferably 50 mol % or more and less than 100 mol %, and more preferably 70 mol % or more and 98 mol % or less. When the content of the acrylic monomer unit is equal to or more than the lower limit, adhesiveness can be easily exhibited. The content of the vinyl monomer unit in the copolymer can be, for example, from 2 mol % to 20 mol %.

[0052] The glass transition temperature of the acrylic resin is preferably 80° C. or lower, more preferably 50° C. or lower, and even more preferably 0° C. or lower. An acrylic resin having a glass transition temperature of more than 80° C. has low adhesion. The glass transition temperature of an acrylic resin is −80° C. or higher, and it is difficult to obtain an acrylic resin having a glass transition temperature lower than that. The glass transition temperature of an acrylic resin can be determined by differential scanning calorimetry or dynamic viscoelasticity measurement. Examples of acrylic monomers that tend to lower the glass transition temperature of acrylic resins include ethyl acrylate, butyl acrylate (particularly n-butyl acrylate), 2-ethylhexyl acrylate, etc. In acrylic resins, the higher the ratio of these monomer units, the lower the glass transition temperature.

[0053] The mass average molecular weight of the acrylic resin is preferably 10,000 to 2,000,000, and more preferably 30,000 to 1,000,000. If the mass average molecular weight of the acrylic resin is equal to or greater than the lower limit, sufficient cohesive strength can be ensured. If the mass average molecular weight is equal to or less than the upper limit, adhesion can be further improved.

[0054] When the acrylic resin has an acrylic monomer unit having a reactive functional group, it may be cured by reacting with a curing agent. When the acrylic resin is cured, the cohesive force of the adhesive layer is improved, and the strength can be improved. In addition, by improving the cohesive force, it is possible to make the adhesive layer removably capable of repeating adhesion and peeling. Examples of the reactive functional group include a hydroxy group, a carboxy group, an amino group, an amide group, an epoxy group, etc. When reacting with a polyfunctional isocyanate described later, the reactive functional group is preferably a hydroxy group, a carboxy group, or an amino group, and more preferably a hydroxy group. Examples of acrylic monomers having a hydroxy group include 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, 3-hydroxypropyl acrylate, 3-hydroxypropyl methacrylate, 4-hydroxybutyl acrylate, and 4-hydroxybutyl methacrylate. Examples of the acrylic monomer having a carboxy group include acrylic acid, methacrylic acid, and itaconic acid. Examples of the acrylic monomer having an amino group include dimethylaminoethyl acrylate, dimethylaminoethyl methacrylate, diethylaminoethyl acrylate, and diethylaminoethyl methacrylate. Examples of acrylic monomers having an amide group include acrylamide, methacrylamide, N-methylol acrylamide, and N-methylol methacrylamide. Examples of the acrylic monomer having an epoxy group include glycidyl acrylate and glycidyl methacrylate. When a polyfunctional isocyanate is used as a curing agent, among the acrylic monomers having a reactive functional group, taking into consideration curability and cost, an acrylic monomer having a hydroxy group is preferred, and 2-hydroxyethyl acrylate and 2-hydroxyethyl methacrylate are more preferred. The acrylic monomer having a reactive functional group that forms the acrylic resin may be of one type or of two or more types.

[0055] (hardening agent) The curing agent may be an isocyanate-based curing agent such as a polyfunctional isocyanate having two or more isocyanate groups in one molecule, or an epoxy-based curing agent such as an epoxy compound having two or more epoxy groups in one molecule. Among these curing agents, polyfunctional isocyanates are preferred from the viewpoint of reactivity. In particular, when the adhesive has an acrylic monomer unit having a hydroxyl group, it is preferred that the curing agent is a polyfunctional isocyanate.

[0056] Examples of the polyfunctional isocyanate include aliphatic polyfunctional isocyanates, alicyclic polyfunctional isocyanates, and aromatic polyfunctional isocyanates. Specific examples of polyfunctional isocyanates include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate, polyphenylene polymethylene polyisocyanate, 1,6-hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, p-phenylene diisocyanate, transcyclohexane 1,4-diisocyanate, 4,4'-dicyclomethane diisocyanate, 3, Examples of the isocyanate include 3'-dimethyl-4,4'-diphenylmethane diisocyanate, dianisidine diisocyanate, m-xylylene diisocyanate, isophorone diisocyanate, 1,5-naphthalene diisocyanate, 1,4-cyclohexane diisocyanate, lysine diisocyanate, lysine ester triisocyanate, tetramethylxylene diisocyanate, 1,6,11-undecane triisocyanate, 1,3,6-hexamethylene triisocyanate, bicyclohepta triisocyanate, and trimethylhexamethylene diisocyanate. The polyfunctional isocyanate may be a modified diisocyanate formed from a modified polyfunctional isocyanate obtained by modifying the diisocyanate so that the NCO / OH molar ratio becomes 2 / 1 or more. The polyfunctional isocyanate may be a modified polyisocyanate. Examples of the modified polyisocyanate include polyurethane polyisocyanates obtained by reacting the polyfunctional isocyanate with polyhydric alcohols, polyisocyanates containing an isocyanurate ring obtained by polymerizing a polyfunctional isocyanate, and polyisocyanates containing a biuret bond obtained by reacting a polyfunctional isocyanate with water. The type of curing agent used for curing the pressure-sensitive adhesive layer may be one type, or two or more types.

[0057] [Base material] The substrate may be a substrate made of an insulating material or a substrate made of a conductive material. The shape of the substrate is not particularly limited, and examples thereof include a shape mainly having a flat surface, such as a film or a substrate. Examples of insulating materials include glass, synthetic resin, and ceramics. The conductive material may be a metal, a conductive metal oxide, carbon, or the like.

[0058] (Film substrate) The film substrate may be, for example, a plastic film made of a synthetic resin, such as ethylene-methyl methacrylate copolymer resin, ethylene-vinyl acetate copolymer resin, polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyvinyl alcohol, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polyacrylate, polycarbonate, polyvinylidene fluoride, polyarylate, styrene-based elastomer, polyester-based elastomer, polyethersulfone, polyetherimide, polyetheretherketone, polyphenylene sulfide, polyimide, cellulose triacetate, cellulose acetate propionate, etc. From the viewpoint of improving the adhesion between the film substrate and the conductive layer, the synthetic resin for the film substrate is preferably a polyester resin, and among these, polyethylene terephthalate is preferable.

[0059] The synthetic resin for the film substrate may be either amorphous or crystalline. The film substrate may be either unstretched or stretched. The film substrate may be subjected to a surface treatment such as a corona discharge treatment, a plasma treatment, or a flame treatment in order to further improve the adhesion of the conductive layer.

[0060] The average thickness of the film substrate is preferably 5 μm to 500 μm, more preferably 20 μm to 200 μm. If the average thickness of the film substrate is equal to or more than the lower limit, the film is less likely to break, and if the average thickness is equal to or less than the upper limit, the film can have sufficient flexibility. The average thickness of the film substrate is calculated by measuring the thickness at 10 randomly selected points and averaging the measured values.

[0061] (Glass substrate) Examples of the glass substrate include an alkali-free glass substrate, a soda-lime glass substrate, a borosilicate glass substrate, and a quartz glass substrate. If the substrate contains an alkali component, the conductivity of the conductive layer tends to decrease, so among the above glass substrates, an alkali-free glass is preferred. Here, the alkali-free glass refers to a glass composition in which the content of the alkali component is 0.1 mass% or less with respect to the total mass of the glass composition.

[0062] The average thickness of the glass substrate is preferably from 100 μm to 3000 μm, more preferably from 100 μm to 1000 μm. If the average thickness of the glass substrate is equal to or more than the lower limit, the substrate is less likely to break, and if the average thickness is equal to or less than the upper limit, the substrate can contribute to a thinner conductive laminate. The average thickness of the glass substrate is calculated by measuring the thickness at 10 randomly selected points and averaging the measured values.

[0063] <Method for manufacturing conductive laminate> A fourth aspect of the present invention is a method for producing a conductive laminate, comprising applying the conductive polymer-containing liquid of the first aspect to at least a part of a surface of a substrate. The conductive laminate of the third aspect can be obtained by the production method of this aspect.

[0064] Examples of a method for applying (coating) the conductive polymer-containing liquid on an arbitrary surface of a substrate include a method using a coater such as a gravure coater, a roll coater, a curtain flow coater, a spin coater, a bar coater, a reverse coater, a kiss coater, a fountain coater, a rod coater, an air doctor coater, a knife coater, a blade coater, a cast coater, or a screen coater; a method using a sprayer such as an air spray, an airless spray, or a rotor dampening; and an immersion method such as dipping.

[0065] The amount of conductive polymer-containing liquid applied to the substrate is not particularly limited, but taking into consideration uniform and even application, conductivity, and film strength, a solid content of 0.01 g / m 2 More than 10.0g / m 2 The following ranges are preferred:

[0066] The conductive layer can be formed by drying the coating film made of the conductive polymer-containing liquid applied onto the substrate to remove at least a portion of the dispersion medium and curing the coating film. Methods for drying the coating film include heat drying, vacuum drying, etc. Examples of heat drying that can be used include hot air heating and infrared heating. When applying heat drying, the heating temperature is appropriately set depending on the dispersion medium used, but is usually within the range of 50° C. to 200° C. Here, the heating temperature is the set temperature of the drying device. A suitable drying time within the above heating temperature range is preferably 0.5 minutes to 30 minutes, more preferably 1 minute to 15 minutes. After drying, UV irradiation may be performed to harden the binder component contained in the coating film.

[0067] When forming a conductive layer on one side of a film substrate and a pressure-sensitive adhesive layer on the other side, a coating material containing a pressure-sensitive adhesive can be applied to the other side to form the pressure-sensitive adhesive layer in the same manner as the conductive layer. The coating material containing a pressure-sensitive adhesive is not particularly limited, and a known coating material can be applied. For example, the coating material containing the above-mentioned acrylic pressure-sensitive adhesive can be used. EXAMPLES

[0068] [Production Example 1] Production of polystyrene sulfonic acid 206 g of sodium styrenesulfonate was dissolved in 1000 ml of ion-exchanged water, and while stirring at 80° C., 1.14 g of an oxidizing agent solution of ammonium persulfate previously dissolved in 10 ml of water was added dropwise over 20 minutes, and the solution was stirred for 12 hours. 1000ml of sulfuric acid diluted to 10% by mass was added to the obtained sodium polystyrene sulfonate-containing solution, and 1000ml of the solvent from the obtained polystyrene sulfonic acid-containing solution was removed by ultrafiltration. Next, 2000ml of ion-exchanged water was added to the remaining liquid, and about 2000ml of the solvent was removed by ultrafiltration to wash the polystyrene sulfonic acid with water. This water washing operation was repeated three times. Water in the resulting solution was removed under reduced pressure to obtain colorless solid polystyrene sulfonic acid.

[0069] [Production Example 2] Production of conductive polymer dispersion containing iron ions A 0.5 g of 3,4-ethylenedioxythiophene (EDOT) and a PSS aqueous solution in which 1.5 g of polystyrene sulfonic acid was dissolved in 15.0 g of ion-exchanged water were mixed at 20° C. Next, 89.5 g of ion-exchanged water was added. The resulting mixed solution was kept at 20°C and, while being stirred, a catalyst solution prepared by dissolving 0.3 g of ferric sulfate in 4.7 g of ion-exchanged water and an oxidant solution prepared by dissolving 1.1 g of ammonium persulfate in 8.9 g of ion-exchanged water were slowly added, and the resulting reaction solution was stirred for 24 hours to cause a reaction. Through the above reaction, a conductive composite (PEDOT-PSS) containing poly(3,4-ethylenedioxythiophene) and polystyrenesulfonic acid, which are π-conjugated conductive polymers, was obtained, along with water as a dispersion medium and a conductive polymer dispersion containing iron ions derived from ferric sulfate. To this conductive polymer-containing liquid, 6.6 g of Duolite C255LFH (a cation exchange resin manufactured by Sumika Chemtex Corporation) and 13.2 g of Duolite A368MS (anion exchange resin manufactured by Sumika Chemtex Corporation) were added, and the ion exchange resin was removed by filtration to obtain a conductive polymer dispersion liquid (non-volatile component concentration 1.3% by mass) from which the oxidant and at least a portion of the catalyst had been removed. The conductive polymer dispersion was then dispersed using a high-pressure homogenizer, and the iron ion content in the resulting conductive polymer dispersion was measured by ICP emission spectrometry, finding it to be 15 ppm.

[0070] [Production Example 3] Production of conductive polymer dispersion containing iron ions B A conductive polymer dispersion (non-volatile component concentration: 1.3 mass %) was obtained in the same manner as in Production Example 2, except that the amount of Duolite C255LFH in Production Example 2 was changed to 13.2 g. The conductive polymer dispersion was then dispersed using a high-pressure homogenizer, and the iron ion content in the resulting conductive polymer dispersion was measured by ICP emission spectrometry, and was found to be 10 ppm.

[0071] [Production Example 4] Production of conductive polymer dispersion containing iron ions C A conductive polymer dispersion (non-volatile component concentration: 1.3 mass %) was obtained in the same manner as in Production Example 2, except that the amount of Duolite C255LFH in Production Example 2 was changed to 19.8 g. Next, the mixture was dispersed using a high-pressure homogenizer, and the amount of iron ions in the resulting conductive polymer dispersion was measured by ICP emission spectrometry, and found to be 5 ppm.

[0072] [Example 1] 10 g of the conductive polymer dispersion of Production Example 4, 65 g of water, 75 g of methanol, and 150 g of isopropanol were mixed and dispersed using a high-pressure homogenizer to obtain a conductive polymer-containing liquid (iron ion content: about 0.17 ppm). The mixture was immediately applied onto a PET film using a #4 bar coater and dried at 120°C for 1 minute to obtain a conductive film. The surface resistance value R 0 The measurement results are shown in Table 1. Next, the obtained conductive polymer-containing liquid was left to stand at 25° C. for 24 hours, and then coated on a PET film using a #4 bar coater and dried at 120° C. for 1 minute to obtain a conductive film. The surface resistance value R 1 The measurement results are shown in Table 1. The conductive polymer-containing liquid obtained in this example had good wettability with respect to the PET film, and no repellency was observed.

[0073] [Example 2] 10 g of the conductive polymer dispersion of Production Example 4, 35 g of water, 75 g of methanol, and 180 g of isopropanol were mixed and dispersed using a high-pressure homogenizer to obtain a conductive polymer-containing liquid (iron ion content: about 0.17 ppm). Thereafter, a conductive film was obtained in the same manner as in Example 1. The results are shown in Table 1.

[0074] [Example 3] 10 g of the conductive polymer dispersion of Production Example 4, 95 g of water, 75 g of methanol, and 120 g of isopropanol were mixed and dispersed using a high-pressure homogenizer to obtain a conductive polymer-containing liquid (iron ion content: about 0.17 ppm). Thereafter, a conductive film was obtained in the same manner as in Example 1. The results are shown in Table 1.

[0075] [Example 4] 10 g of the conductive polymer dispersion of Production Example 4, 35 g of water, 105 g of methanol, and 150 g of isopropanol were mixed and dispersed using a high-pressure homogenizer to obtain a conductive polymer-containing liquid (amount of iron ions in water: about 0.17 ppm). Then, a conductive film was obtained in the same manner as in Example 1. The results are shown in Table 1.

[0076] [Example 5] 10 g of the conductive polymer dispersion of Production Example 4, 95 g of water, 45 g of methanol, and 150 g of isopropanol were mixed and dispersed using a high-pressure homogenizer to obtain a conductive polymer-containing liquid (iron ion content: about 0.17 ppm). Thereafter, a conductive film was obtained in the same manner as in Example 1. The results are shown in Table 1.

[0077] [Comparative Example 1] 10 g of the conductive polymer dispersion of Production Example 4, 65 g of water, and 225 g of methanol were mixed and dispersed using a high-pressure homogenizer to obtain a conductive polymer-containing liquid (iron ion content: about 0.17 ppm). Thereafter, a conductive film was obtained in the same manner as in Example 1. The results are shown in Table 1. The conductive polymer-containing liquid obtained in this example had poor wettability with respect to the PET film, and was repelled, making it difficult to form a large-area conductive layer with a uniform thickness.

[0078] [Comparative Example 2] 10 g of the conductive polymer dispersion of Production Example 4, 65 g of water, and 225 g of isopropanol were mixed and dispersed using a high-pressure homogenizer to obtain a conductive polymer-containing liquid (iron ion content: about 0.17 ppm). Since the conductive complex immediately precipitated thereafter, further investigation was discontinued.

[0079] [Example 6] 10 g of the conductive polymer dispersion of Production Example 3, 65 g of water, 75 g of methanol, and 150 g of isopropanol were mixed and dispersed using a high-pressure homogenizer to obtain a conductive polymer-containing liquid (iron ion content: about 0.33 ppm). The mixture was immediately applied onto a PET film using a #4 bar coater and dried at 120°C for 1 minute to obtain a conductive film. The surface resistance value R of this conductive film was 0 The measurement results are shown in Table 1. Next, the obtained conductive polymer-containing liquid was left to stand at 25° C. for 24 hours, and then coated on a PET film using a #4 bar coater and dried at 120° C. for 1 minute to obtain a conductive film. The surface resistance value R 1 The measurement results are shown in Table 1. The conductive polymer-containing liquid obtained in this example had good wettability with respect to the PET film, and no repellency was observed.

[0080] [Example 7] 10 g of the conductive polymer dispersion of Production Example 3, 35 g of water, 75 g of methanol, and 180 g of isopropanol were mixed and dispersed using a high-pressure homogenizer to obtain a conductive polymer-containing liquid (iron ion content: about 0.33 ppm). Thereafter, a conductive film was obtained in the same manner as in Example 6. The results are shown in Table 1.

[0081] [Example 8] 10 g of the conductive polymer dispersion of Production Example 3, 95 g of water, 75 g of methanol, and 120 g of isopropanol were mixed and dispersed using a high-pressure homogenizer to obtain a conductive polymer-containing liquid (iron ion content: about 0.33 ppm). Thereafter, a conductive film was obtained in the same manner as in Example 6. The results are shown in Table 1.

[0082] [Example 9] 10 g of the conductive polymer dispersion of Production Example 3, 35 g of water, 105 g of methanol, and 150 g of isopropanol were mixed and dispersed using a high-pressure homogenizer to obtain a conductive polymer-containing liquid (iron ion content: about 0.33 ppm). Then, a conductive film was obtained in the same manner as in Example 6. The results are shown in Table 1.

[0083] [Example 10] 10 g of the conductive polymer dispersion of Production Example 3, 95 g of water, 45 g of methanol, and 150 g of isopropanol were mixed and dispersed using a high-pressure homogenizer to obtain a conductive polymer-containing liquid (iron ion content: about 0.33 ppm). Thereafter, a conductive film was obtained in the same manner as in Example 6. The results are shown in Table 1.

[0084] [Comparative Example 3] 10 g of the conductive polymer dispersion of Production Example 3, 65 g of water, and 225 g of methanol were mixed and dispersed using a high-pressure homogenizer to obtain a conductive polymer-containing liquid (iron ion content: about 0.33 ppm). Thereafter, a conductive film was obtained in the same manner as in Example 6. The results are shown in Table 1. The conductive polymer-containing liquid obtained in this example had poor wettability with respect to the PET film, and was repelled, making it difficult to form a large-area conductive layer with a uniform thickness.

[0085] [Comparative Example 4] 10 g of the conductive polymer dispersion of Production Example 3, 65 g of water, and 225 g of isopropanol were mixed and dispersed using a high-pressure homogenizer to obtain a conductive polymer-containing liquid (iron ion content: about 0.33 ppm). Since the conductive complex immediately precipitated thereafter, further investigation was discontinued.

[0086] [Comparative Example 5] 10 g of the conductive polymer dispersion of Production Example 2, 65 g of water, 75 g of methanol, and 150 g of isopropanol were mixed and dispersed using a high-pressure homogenizer to obtain a conductive polymer-containing liquid (iron ion content: 0.50 ppm). The mixture was immediately applied onto a PET film using a #4 bar coater and dried at 120°C for 1 minute to obtain a conductive film. The surface resistance value R 0 The measurement results are shown in Table 1. Next, the obtained conductive polymer-containing liquid was left to stand at 25° C. for 24 hours, and then coated on a PET film using a #4 bar coater and dried at 120° C. for 1 minute to obtain a conductive film. The surface resistance value R 1 The measurement results are shown in Table 1. The conductive polymer dispersion obtained in this example had good wettability with respect to the PET film, and no repellency was observed.

[0087] [Comparative Example 6] 10 g of the conductive polymer dispersion of Production Example 2, 35 g of water, 75 g of methanol, and 180 g of isopropanol were mixed and dispersed using a high-pressure homogenizer to obtain a conductive polymer-containing liquid (iron ion content: 0.50 ppm). Thereafter, a conductive film was obtained in the same manner as in Comparative Example 5. The results are shown in Table 1.

[0088] [Comparative Example 7] 10 g of the conductive polymer dispersion of Production Example 2, 95 g of water, 75 g of methanol, and 120 g of isopropanol were mixed and dispersed using a high-pressure homogenizer to obtain a conductive polymer-containing liquid (iron ion content: 0.50 ppm). Thereafter, a conductive film was obtained in the same manner as in Comparative Example 5. The results are shown in Table 1.

[0089] [Comparative Example 8] 10 g of the conductive polymer dispersion of Production Example 2, 35 g of water, 105 g of methanol, and 150 g of isopropanol were mixed and dispersed using a high-pressure homogenizer to obtain a conductive polymer-containing liquid (iron ion content: 0.50 ppm). Thereafter, a conductive film was obtained in the same manner as in Comparative Example 5. The results are shown in Table 1.

[0090] [Comparative Example 9] 10 g of the conductive polymer dispersion of Production Example 2, 95 g of water, 45 g of methanol, and 150 g of isopropanol were mixed and dispersed using a high-pressure homogenizer to obtain a conductive polymer-containing liquid (iron ion content: 0.50 ppm). Thereafter, a conductive film was obtained in the same manner as in Comparative Example 5. The results are shown in Table 1.

[0091] [Comparative Example 10] 10 g of the conductive polymer dispersion of Production Example 2, 65 g of water, and 225 g of methanol were mixed and dispersed using a high-pressure homogenizer to obtain a conductive polymer-containing liquid (iron ion content: 0.50 ppm). Thereafter, a conductive film was obtained in the same manner as in Comparative Example 5. The results are shown in Table 1. The conductive polymer-containing liquid obtained in this example had poor wettability with respect to the PET film, and was repelled, making it difficult to form a large-area conductive layer with a uniform thickness.

[0092] [Comparative Example 11] 10 g of the conductive polymer dispersion of Production Example 2, 65 g of water, and 225 g of isopropanol were mixed and dispersed using a high-pressure homogenizer to obtain a conductive polymer-containing liquid (iron ion content: 0.50 ppm). Since the conductive complex immediately precipitated thereafter, further investigation was discontinued.

[0093] [Surface resistance measurement] For the conductive film produced in each example, the surface resistance R of the conductive layer 0 and R 1 was measured using a resistivity meter (Hiresta manufactured by Nitto Seiko Analytech Co., Ltd.) under the condition of an applied voltage of 10 V. In the table, "1.0E+07" means "1.0 x 10 7" and so on. In the table, the MeOH / IsoOH ratio indicates the mass ratio of methanol and isopropanol contained in the conductive polymer-containing liquid used, and the increase rate is the surface resistance R 1 / R 0 Represents a ratio.

[0094] [Table 1]

[0095] Example 11 10g of the conductive polymer dispersion of Production Example 4 was mixed with 65g of water, 75g of methanol, and 150g of isopropanol, dispersed using a high-pressure homogenizer, and then 10g of PES RESIN A-645GH (manufactured by Takamatsu Oil Co., Ltd., epoxy group-containing acrylic resin and polyester resin liquid, solid content 30%, water-dispersed emulsion) was mixed in to obtain a conductive polymer-containing liquid (iron ion amount: about 0.16 ppm). Immediately, the mixture was applied to a PET film using a #4 bar coater and dried at 120°C for 1 minute to obtain a conductive film. The surface resistance value R of this conductive film was 1000 g. 0 The measurement results are shown in Table 2. Next, the obtained conductive polymer-containing liquid was left to stand at 25° C. for 24 hours, and then applied to a PET film using a #4 bar coater and dried at 120° C. for 1 minute to obtain a conductive film. The surface resistance value R 1 The measurement results are shown in Table 2. The conductive polymer-containing liquid obtained in this example had good wettability with respect to the PET film, and no repellency was observed.

[0096] Example 12 A conductive film was produced and evaluated in the same manner as in Example 11, except that the conductive polymer dispersion liquid in Production Example 4 was changed to the conductive polymer dispersion liquid in Production Example 3 to obtain a conductive polymer-containing liquid (iron ion content: about 0.32 ppm). The results are shown in Table 2.

[0097] Comparative Example 12 A conductive film was produced and evaluated in the same manner as in Example 11, except that the conductive polymer dispersion liquid in Production Example 4 was changed to the conductive polymer dispersion liquid in Production Example 2 to obtain a conductive polymer-containing liquid (iron ion content: about 0.48 ppm). The results are shown in Table 2.

[0098] [Table 2]

[0099] Example 13 An adhesive solution was obtained by mixing 60 g of an acrylic adhesive (SK Dyne 1499M, manufactured by Soken Chemical Industries, Ltd., solids concentration 35 mass%, ethyl acetate / butyl acetate mixed solution), 1.62 g of a toluene diisocyanate-trimethylolpropane adduct (L-45, manufactured by Soken Chemical Industries, Ltd., solids concentration 45 mass%, toluene / ethyl acetate mixed solution) as a curing agent, and 40 g of methyl ethyl ketone. The obtained adhesive solution was applied to the surface opposite to the conductive layer of the conductive film obtained in Example 1 using a #16 bar coater, and dried for 1 minute at 100° C. The adhesive strength of the adhesive layer side at this time was measured and found to be 0.13 N / cm.

[0100] <Result> In the conductive polymer-containing liquid of each example according to the present invention, the amount of iron ions was 0.34 ppm or less, so that the conductive complex was sufficiently dispersed in the dispersion medium containing methanol and isopropanol, and the dispersion stability was excellent. As a result, the conductivity of the conductive layer formed by coating after leaving it to stand for 24 hours was also good. The conductive polymer-containing liquids of Comparative Examples 1, 3, and 10 did not contain isopropanol, and therefore had poor wettability to the film substrate, making it difficult to form a conductive layer of uniform thickness over a large area or a desired area. The conductive polymer-containing liquids of Comparative Examples 2 and 4 did not contain methanol, and therefore it was difficult to disperse the conductive complex. Since the conductive polymer-containing liquid in Comparative Examples 5 to 9 contained a large amount of iron ions, the dispersion stability of the conductive complex was poor, and the conductivity of the conductive layer formed by coating after leaving it to stand for 24 hours was significantly deteriorated.

Claims

1. A conductive polymer-containing liquid containing a conductive complex including a π-conjugated conductive polymer and a polyanion, and a dispersion medium, The dispersion medium contains water, methanol, and isopropanol; The total content of the methanol content m1 and the isopropanol content m2 with respect to the total mass of the dispersion medium is 60 mass% or more; The content of the water (m3) relative to the total mass of the dispersion medium is 10% by mass or more; a mass ratio of the content m1 of the methanol to the content m2 of the isopropanol in the dispersion medium, expressed as (m1 / m2), is 0.1 to 0.9; A conductive polymer-containing liquid, wherein the content of iron ions relative to the total mass of the conductive polymer-containing liquid is 0.34 ppm or less.

2. A reaction solution containing a polyanion, an aqueous dispersion medium, a monomer for forming a π-conjugated conductive polymer, and iron ions is used to polymerize the monomer, obtaining a conductive polymer dispersion (A) containing a conductive complex containing the π-conjugated conductive polymer and the polyanion, the aqueous dispersion medium, and the iron ions; a step of adding a cation exchange resin to the conductive polymer dispersion (A) to adsorb at least a portion of the iron ions, and then removing the cation exchange resin to obtain a conductive polymer dispersion (B); and adding at least methanol and isopropanol to the conductive polymer dispersion liquid (B) to obtain a conductive polymer-containing liquid, a content of the iron ions relative to the total mass of the conductive polymer dispersion (B) is less than 10 ppm, and a content of the iron ions relative to the total mass of the conductive polymer-containing liquid is 0.34 ppm or less.

3. A conductive layer formed on one surface of the film substrate and comprising a cured layer of the conductive polymer-containing liquid according to claim 1 or 2, A conductive laminate optionally provided with a pressure-sensitive adhesive layer on the other surface of the film substrate.

4. A method for producing a conductive laminate, comprising applying the conductive polymer-containing liquid according to claim 1 or 2 to at least a partial surface of a substrate.

Citation Information

Patent Citations

  • Composition for electroconductive coating and aqueous dispersion containing conductive polymer

    JP2010018698A

  • Electroconductive polymer / dopant dispersion, electroconductive composition and electroconductive film

    JP2011208016A

  • Polythiophene-based conductive polymer film

    JP2011500936A

  • Conductive polymer aqueous dispersion liquid, alcohol containing conductive polymer aqueous dispersion liquid, and method for producing conductive film

    JP2017057335A

  • Method for producing conductive polymer dispersion liquid and method for producing conductive film

    JP2017125096A